Occupational Asthma - Sigsgaard, Torben; Heederik, Dick.; SpringerLink (Online service) (Basel : Birkhäuser Basel : Imprint: Birkhäuser, 2010)
Recent developments in the field of occupational asthma research and clinical practice are the topic of this volume. The contribution of occupational exposures to chemical and biological agents to the burden of asthma in adults is clearly described in an overview of the most recent epidemiological data from both general population and industry based studies. Emphasis is put on powerful approaches like the use of apprentices studies, which include young individuals, naïve with regard to occupational exposures. Diagnostic criteria for work related and work aggravated asthma are introduced and the latest insights in underlying mechanisms are covered as well. Specific emphasis is given to exposure response relationships for allergen exposure, which opens opportunities for primary and secondary prevention. Large gene-environment studies are undertaken for asthma and their contribution to understanding occupational asthma is discussed. Specific attention is given to whole genome screening approaches which involve with present technological possibilities the analysis of thousands of single nucleotide polymorphisms, versus the more focused candidate gene approach where genes with potential mechanistic plausibility are considered. Although the latter approach has been used more extensively, whole genome screening studies are becoming available soon, also for studies on occupational asthma. Management, prevention and surveillance are covered as well. All three areas are undergoing some changes in perception because of the exposure response relationships unraveled during the last decade. Diagnostic rules are introduced to rationalize the diagnostic workup and improve the cost benefit of surveillance schemes, and in preventive measures at large. This approach is only recently introduced in the field of occupational asthma and is expected to contribute even more in the coming years. Population studies, either general population studies, or work force based studies, have contributed enormously to our understanding of disease etiology and in the costs related to the disease. Issues in the design of such studies are discussed to assist the readers in designing and conducting their own study. Altogether this book gives a comprehensive insight in the present developments which will change the occupational asthma field the coming years.
The history of research on asthma in the workplace — Development, victories and perspectives -- Epidemiology and risk factors of occupational respiratory asthma and occupational sensitization -- Epidemiology of laboratory animal allergy -- Population-attributable fraction for occupation and asthma -- Definition and diagnosis of occupational asthma -- Work-exacerbated asthma -- Natural history and prognosis -- Mechanisms of allergic occupational asthma -- Mechanisms of occupational asthma caused by low-molecular-weight chemicals -- Asthma-like diseases in agriculture -- Allergen and irritant exposure and exposure-response relationships -- Gene-environment interactions in occupational asthma -- Asthma in apprentice workers The birth cohort parallel: Using apprentices as a powerful cohort design for studying occupational asthma -- Management of an individual worker with occupational asthma -- Social consequences and quality of life in work-related asthma -- Prevention of work-related asthma seen from the workplace and the public health perspective -- Prevention and regulatory aspects of exposure to asthmagens in the workplace -- Design, conduct and analysis of surveys on work-related asthma.
Keywords: Occupational medicine; Respiratory organs—Diseases.; Immunology; Pharmacology; Allergy; Occupational Medicine/Industrial Medicine; Pneumology/Respiratory System; Immunology; Pharmacology/Toxicology.; Allergology